Magnetic Field Effect on Growth and Antibiotic Susceptibility of Staphylococcus aureus. - Kamel, Fouad Houssein; Saeed, Chiman Hameed; Qader, Saleem Saaed (Al-Nahrain Journal of Science, 2018)
It is aimed to investigate the effect of exposure of different magnetic fields (400, 800.1200 and 1600 Gauss for 2 to 24 hours) on the growth rate and antibiotic sensitivity of Staphylococcus aureus. The experiments were done in Hawler Medical Research Centre Erbil, Iraq. The bacteria were isolated from medical case in Rizgary hospital and identified using API STAPH system. The antibiotic susceptibility of Staphylococcus aureus measured according to Kirby-Bauer disc diffusion technique. Results showed a significant decrease in the logarithm in the number of Staph. aureus (41.4 to 27 X 106) treated with high frequency magnetic field. Sensitivity of Staph.aureus to antibiotic increase during a short period (4-6 hours) and increase its resistance to same antibiotic at log term of exposure (18-24 hours). Some results of biochemical tests also showed positive effects of magnetic fields on the biochemical properties according to API STAPH results. The bacterial enzymes MAL (Maltose), LAC (Lactose), TRE (D-Trehalose), MAN (D-Mannitol), SAC (Sucrose) and NAG (N-acetyl-glucosamine) were affected by magnetic field at 24 hours of incubation.It is concluded that the cellular membrane of the microorganism had been affected by the magnetic field, also the response increased when the field intensity increased. So the magnetic field effects on bacteria are considered bactericidal, and hence, a change in the number of the cells per ml or the measured change in the membrane sensitivity to antibiotic demonstrated also the change in the internal structure of the cells.